Size‐Controlled Formation of Noble‐Metal Nanoparticles in Aqueous Solution with a Thiol‐Free Tripeptide. Issue 30 (21st April 2016) - Corra, Stefano; Lewandowska, Urszula; Benetti, Edmondo M.; Wennemers, Helma
Abstract: A combinatorial screening revealed the peptide H‐His‐d ‐Leu‐d ‐Asp‐NH2 (1 ) as an additive for the generation of monodisperse, water‐soluble palladium nanoparticles with average diameters of 3 nm and stabilities of over 9 months. The tripeptide proved to be also applicable for the size‐controlled formation of other noble‐metal nanoparticles (Pt and Au). Studies with close analogues of peptide 1 revealed a specific role of each of the three amino acids for the formation and stabilization of the nanoparticles. These data combined with microscopic and spectroscopic analyses provided insight into the structure of the self‐assembled peptidic monolayer around the metal core. The results open interesting prospects for the development of functionalized metal nanoparticles. Abstract : A coat of peptides : Monodisperse Pd‐, Pt‐, and AuNPs were formed in aqueous solution in the presence of a thiol‐free tripeptide. The NPs were stable for months as a result of the formation of a compact peptidic monolayer around the metal core within which each amino acid fulfills a specific role.